(untitled) (Economics and region, 2022)
The industrial sector plays an important role in ensuring innovative development and integration of the national economy into the world. It acts as a source of innovative products, which are mastered by agricultural, mining, industrial and construction enterprises, as well as by economic entities in the service sector. In developed countries, the development of industry has always been among the key priorities. Although Ukraine historically had an industrial-type economy, a model of agrarian and raw material development was built during the years of independence. This led to technical and technological backwardness, a decrease in productivity and actual defenselessness in the face of external military aggression from the Russian Federation. The question of the post-war recovery of the industrial sector should not be considered only in the context of the return of production to pre-war characteristics. This is a chance to carry out structural reforms, transition to production of goods with high added value and export of high-tech products. The purpose of this article is to analyze the main indicators of the functioning of the Ukrainian industry and to identify, based on the criteria of sectoral priorities, industries-drivers of innovative development. The article analyzes the key indicators of the functioning of Ukrainian industry in the pre-war period. The special role of the processing industry, which forms the conditions for innovative development with the help of cross-industry interactions, is emphasized. It has been established that the processing industry is responsible for capital formation of all types of economic activity. In accordance with KVED-2010, the types of economic activity in the processing industry of Ukraine were analyzed according to the following criteria: the contribution of the processing industry to the growth of macroeconomic indicators, the innovativeness of the industry, the multiplier effect of the industry on the economy, competitive advantages of products of the processing industry on the foreign market. The priority branches of the processing industry, which act as drivers of innovative development of the economy of Ukraine, have been determined.